2002
DOI: 10.1007/s00204-002-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of olfactory toxicants on olfactory regeneration

Abstract: The aim was to study the long-term response in the olfactory mucosa of NMRI mice after exposure to the olfactory toxicants dichlobenil (a herbicide) or methimazole (an antithyroid drug). Three and six months after exposure to dichlobenil (2x or 1 x 25 mg/kg i.p.), the dorsomedial part of the olfactory region showed a respiratory metaplasia with abundant invaginations and a fibrotic lamina propria. In contrast, 3 months after exposure to a toxic dose of methimazole (2 x 50 mg/kg i.p.), the olfactory neuroepithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 44 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…At the OE level, the dorso-ventral organization of the different OSNs populations is completely restored [45]. However, these methods damage the LP and produce metaplasia of supportive tissue of the OE [5], [6]. At the OB, few axon fibers reach the dorsal part [5] and the specific glomerular organization is disrupted [36], [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the OE level, the dorso-ventral organization of the different OSNs populations is completely restored [45]. However, these methods damage the LP and produce metaplasia of supportive tissue of the OE [5], [6]. At the OB, few axon fibers reach the dorsal part [5] and the specific glomerular organization is disrupted [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that methimazole is metabolized by a cytochrome P450 in sustentacular cells and Bowman glands, causing massive apoptosis and promoting the degeneration of OE supportive cells [6], [51], [52]. This leads to detachment of OSNs while progenitor cells remain intact [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recovery from zinc sulfate lesion was less efficient in adult (6 month old) mice than in young (1 month old) mice (Ducray et al, 2002a), but functional recovery occurred even in the adult group (Ducray et al, 2002b). However, chemical lesions are not equivalent in the amount of damage they cause (Bergman et al, 2002). Using a different lesion method (3,3′-iminodipropionitrile; IDPN), Genter and Ali (1998) demonstrated that there is an age-related susceptibility to damage caused by IDPN, perhaps confounding the interpretation of chemical lesion results in aged mice (Bovetti et al, 2011).…”
Section: The Effect Of Organismal Age On the Regenerative Capacity Ofmentioning
confidence: 99%